"According to the Strict Principles of Honor": Loyalty, Ambition, and Service in the Habsburg Army during the Coalition Wars. (May 2022) - Baird, Kurt J. G.
Abstract: This article examines the lived experience of the Habsburg's military institutions in the lead-up to the Austro-Franco war of 1809, a period in which military service was positioned as the most loyal act a dutiful male subject of the emperor Francis I (II) could undertake. It does this by paying particular attention to a shameful and embarrassing public military display and the resulting near-violent dispute between company officers of the Jordis infantry regiment, as recorded and reflected upon by a young junior officer in 1808. This account allows for the examination of the ways in which honor created narrative frameworks and communities that persuaded diverse individuals to place their experiences within the context of the monarchy's war with France.